TLR2 and TLR4 in Ischemia Reperfusion Injury. (16th May 2010) - Arslan, F.; Keogh, B.; McGuirk, P.; Parker, A. E.
Abstract : Ischemia reperfusion (I/R) injury refers to the tissue damage which occurs when blood supply returns to tissue after a period of ischemia and is associated with trauma, stroke, myocardial infarction, and solid organ transplantation. Although the cause of this injury is multifactorial, increasing experimental evidence suggests an important role for the innate immune system in initiating the inflammatory cascade leading to detrimental/deleterious changes. The Toll-like Receptors (TLRs) play a central role in innate immunity recognising both pathogen- and damage-associated molecular patterns and have been implicated in a range of inflammatory and autoimmune diseases. In this paper, we summarise the current state of knowledge linking TLR2 and TLR4 to I/R injury, including recent studies which demonstrate that therapeutic inhibition of TLR2 has beneficial effects on I/R injury in a murine model of myocardial infarction.